Aspergillus identification through bronchoscope in intensive care unit – a retrospective, databased cohort study - Hsin-I Cheng; Chun-Yu Lin; Chun-Yu Lin; Horng-Chyuan Lin; Horng-Chyuan Lin; Horng-Chyuan Lin; Shu-Min Lin; Shu-Min Lin; Shu-Min Lin; Shu-Min Lin; Meng-Heng Hsieh; Meng-Heng Hsieh; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionInvasive pulmonary aspergillosis (IPA) increases the risk of mortality of critically ill patients. Diagnostic criteria specifically targeting patients in intensive care units(ICUs) have been developed to improve diagnostic sensitivity. This study investigated health outcomes among patients in ICUs with Aspergillus isolates identified using bronchoscopy.MethodsThis retrospective cohort study obtained data from the Chang Gung Research Database of Chang Gung Memorial Hospital. Patients admitted to the ICU between January 2017 and December 2022 who received bronchoalveolar lavage were enrolled. Patients with a fungus culture yielding Aspergillus spp. isolates or who had an Aspergillus galactomannan antigen index value of >1.0 were categorized into the Aspergillus-positive group.ResultsA total of 2372 patients were enrolled, and 146 patients (6.16%) tested positive for Aspergillus. Of the patients who tested positive for Aspergillus, 37.67% had a positive culture result, and 77.4% had a positive galactomannan antigen result. Patients with Aspergillus isolates were more likely to have a recent influenza infection, concurrent bacterial sepsis, and a cavitation and to die in hospital (in-hospital mortality rate 58.9% vs. 48.57%, P = 0.016).DiscussionIdentifying Aspergillus through bronchoscopy in the ICU is associated with higher mortality rates than in patients who test negative for Aspergillus. Galactomannan antigen from bronchoalveolar lavage may provide higher diagnostic sensitivity.